KONTRIBUSI PELESTARIAN HUTAN MANGROVE TERHADAP TINGKAT PENDAPATAN ANGGOTA KELOMPOK PENGELOLA (KPM) BELUKAP DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - Nahor, Ismenni Banjar; Yoza, Defri; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Mangrove forests are important life-supporting ecosistem in coastal areas. According to Macnae (1968), mangrove is defined as a group of vegetation that grow between the highest water level during high tide and the lowest water level during low tide. At Teluk Pambang village, an organization called Kelompok Pengelola Mangrove (KPM) Belukap was formed due to the anxiety of nearby people to further irresponsible demage of mangrove forests. After the co-fish project, a group was created to manage and project mangrove forests for fishery activities. This research aims to study the contribution of mangrove forest conservation to the income of KPM Belukap at Teluk Pambang village, Kecamatan Bantan, Kabupaten Bengkalis, Riau Province. Contribution of mangrove forest conservation and income data were collected, tabulated, analyzed. Income data were collected descriptively using survey papers. Analysis result show that the conservation of mangrove forests increase the income of KPM Belukap by 1,20% to 3,75%. Â  Keywords: Contributions, Mangrove Forest, Income, Conservation